Cibernética e convivencialidade: integração entre conversações paralelas como estratégia para auto-organização - Marcus Vinicius Augustus Fernandes Rocha Bernardo (2021)
In search of useful knowledge for collective management strategies, this research correlates the concept of conviviality, as conceived by the philosopher Ivan Illich in 1972, with the systemic thinking spread from the end of the Second World War. The thesis presents how, through cybernetics, system thinking has radically changed several fields of knowledge and has affected and can still affect in different ways what Illich calls conviviality. One of these ways, explored further during the research, is the Team Sintegrity protocol — a strategy for holding meetings in large groups. Throughout the text, Illich's work is historically correlated with Cybernetics through addressing mutual collaborations throughout the 1970s, criticisms made during the 1980s and an apparent theoretical alignment between these criticisms and those that already existed within the field itself, in the branch known as Second Order Cybernetics. From this theoretical-historical introduction, practices are presented that correlate the various concepts worked on, in short: conviviality, conversation, radical constructivism and the Team Sintegrity protocol. The main conclusion is that the principles of constructivism and conviviality, in order to be practically viable in decision-making processes, need adequate methods of negotiation.